Video Game and Internet Addiction in Mexican High School Students - Portillo-Peñuelas, Samuel Alejandro (2023)
Introduction. The indiscriminate use of Information and Communication Technologies in modern society has led to dependence on technological devices and their connectivity to the Internet, particularly for leisure and entertainment. Objectives. This study aims to (1) identify the prevalence of internet and video game addiction among high school students in Mexico, and (2) explore associations between addiction levels, gender, context (urban/rural), and age. Method. A non-experimental, cross-sectional study design with a descriptive-correlational approach was employed. An incidental sample of 419 students completed the Internet and Video Game Addiction Questionnaire for Adolescents (CAIVA) developed by Chahín-Pinzón & Briñez (2018). Findings. The analysis revealed that students exhibited low levels of addiction to video games and the Internet. Additionally, it was observed that males had higher levels of addiction to video games. Furthermore, no significant differences were noted between students from urban and rural contexts in both cases. Finally, significant negative correlations were identified between these variables and age. Conclusions. In general, while the majority of participants fell into the category without addiction to video games and the Internet, those exhibiting addiction tended to show a decrease in prevalence as they aged. Men were found to be more susceptible to video game addiction, whereas women were more prone to Internet addiction. It is pertinent to expand the current research trajectory by incorporating additional variables and methodologies that positively impact the reduction of this issue.